Evaluation of Coorg mandarin (Citrus reticulata) clones for yield and quality - TRIPATHI, P C; KARUNAKARAN, G; SAKTHIVEL, T; RAVISHANKAR, H; SANKAR, V; KUMAR, R SENTHIL (The Indian Journal of Agricultural Sciences, 2016)
Coorg mandarin (Citrus reticulata Blanco) is acclaimed for its exquisite taste, quality, distinct flavour and keeping quality. It is predominantly grown, as an intercrop in the coffee-based cropping system in Kodagu region of Karnataka since more than a century. The area of Coorg mandarin was drastically reduced during last two decades due to Phytophthora, Citrus Tristeza Virus (CTV) and Citrus Greening Disease (CGD). An extensive field survey was undertaken in different Coorg mandarin growing regions and 20 high yielding diseases - free superior clones were identified. These clones were planted for field evaluation in randomized block design (RBD) during September 2006 at CHES, Chettalli. The growth observations revealed that the average plant height was maximum in Clone -13 (2.72 m) for 9 years followed by Clone - 7 (2.55 m) and Clone -11 (2.55 m). The rootstock and union ratio was between 0.98 to 1.02 while rootstock scion ratio ranged between 0.87 and 0.91. This indicates that there is no incompatibility with rootstock in all selected clones. The maximum rootstock girth (22.77 cm) and scion girth (20.02 cm) was recorded in Clone -7. The tree volume ranged from 3.40 m3 in Clone-19 to 5.17 m3 in Clone -4. The Clone - 4, Clone-13, Clone-7, Clone-10 were found vigorous while Clone-19, Clone-18, Clone-6 were found least vigorous. The highest average yield was recorded in Clone –8 (14.82 kg/plant) while lowest yield was recorded in Clone -18 ( 8.5 kg/plant). The average fruit weight ranged from 96.78 g (Clone-14) to 130.84g (Clone-8). The number of seeds per fruit was lowest in Clone –3 (11.1). TSS was the highest (9.54oB) in Clone -17 and Clone – 8 (9.13 oB). The pulp per cent was highest in Clone -15 (75.3 %). The fruits of Clone- 1 recorded the highest ascorbic acid content of 38.3 mg/100 ml of juice while Clone- 13 registered the minimum (25.69 mg/100 ml). The results revealed Clone-8 and Clone-20 were found better for yield and some of the fruit quality characters. These can be utilized for commercial cultivation while other clones which are superior in one or other traits may be utilized in breeding programmes.